To Shudder in the Sign of Mimesis Towards a Recovery of Unreduced Experience in Theodor W. Adorno (Itinera, 2024)
In the last decades, an enthusiastic and undivided attention has been firmly dedicated to Adorno’s notion of mimesis. Highly enigmatic and resistant to an easy comprehension, this concept has often been regarded as a fundamental cornerstone of Adorno’s philosophy. In actual fact, the meanings and uses he has endowed the term with are so pervasive and diffuse that its imbrication in Adorno’s main philosophemes transcends the strict realm of art, showing a substantial entanglement between the aesthetic dimension and the epistemic, the anthropological and the social ones. More precisely, this paper aims to investigate his specific conception of mimesis as that faculty that could contribute to heal that historical process of experiential impoverishment that affects modern life. To the mimetic comportment Adorno associates a productive openness to the other that allows the subject to touch and to be touched by the object, without coercively subsuming it. Thereby, through a renewed interplay between mimesis and rationality, Adorno hopes to restore the possibility of a full and unreduced experience.
Keywords: Adorno, mimesis, experience, shudder